Risk of Obesity for Hypertension differs between Diabetic and Non-diabetic Subjects (Ibrahim Medical College Journal, 2009)
In recent years, non-communicable diseases (NCD) like obesity, hypertension (HTN) and Type2 diabetes (T2DM) are on the increase, specially in the developing nations. Body mass index (BMI), waist-to-hip ratio (WHR) and Waist-to-height ratio (WHtR) are used as indices of obesity to relate T2DM, HTN and coronary artery disease (CAD). This study addresses whether the risk of obesity for HTN differs between T2DM and non-DM subjects. We investigated 693 diabetic patients from BIRDEM and 2384 from communities. We measured height, weight, waist-girth, hip-girth and blood pressure. All subjects underwent oral glucose tolerance test (OGTT). BMI, WHR and WHtR were calculated. Systolic and diastolic hypertension (sHTN and dHTN)) were defined as SBP >=140 and DBP >= 90 mmHg, respectively. The prevalence of both sHTN and dHTN in T2DM was higher than the non-DM subjects (sHTN: 49.1 vs 14.3%, dHTN 19.6 vs. 9.5%). The comparison of characteristics between subjects with and without hypertension showed that the differences were significant for age, weight, waist-girth, BMI, WHR and WHtR for both T2DM and non-DM subjects (for all p < 0.001). The increasing trend of hypertension with increasing obesity was observed more in the non-DM than in the T2DM subjects. The risk (OR) of obesity for hypertension increased with increasing WHR and WHtR in the non-DM than the T2DM subjects. Compared with the non-DM the T2DM participants had two to three folds higher prevalence of HTN. In either group, BMI, WHR and WHtR were significantly higher in the hypertensive than the non-hypertensive subjects. The prevalence of hypertension increased with the increasing BMI, WHR and WHtR but significant only in the non-DM. Further studies may confirm these findings and determine whether there was any altered association between blood pressure and obesity in diabetes possibily, with or without autonomic neuropathy. Ibrahim Med. Coll. J. 2007; 1(1): 1-6 Key words: obesity, hypertension, diabetes, odds ratio   doi: 10.3329/imcj.v1i1.2887